Investigation on vibration of Centrifugal Pump by Bearing supported position. Issue 1 (1st February 2022) - Sun, Tao; Liu, Songge; Yu, Wanbo; Shi, Zhenyi
Abstract: Vibration is one of the main problems which should be considered seriously in designing and operating a marine centrifugal pump to decrease vibration for the reliability of equipment and safety of ship. The reduction for vibration also can provide a guarantee for enhancing concealment, which will be benefit for military ships with higher requirements for concealment to improve combat effectiveness. A numerical calculation model of whole centrifugal pump was established in this paper. The emphasis of this article is that influence of bearing supported position on vibration of centrifugal pump. And conclusion was obtained that vibration peak can be reduced through adjust supported position of bearing reasonably. The simulation results was proved by experiment which was carried out in the Shaking Table Test.